First observations of the structure and megafaunal community of a large Lophelia reef on the Ghanaian shelf (the Gulf of Guinea). (March 2017) - Buhl-Mortensen, L.; Serigstad, B.; Buhl-Mortensen, P.; Olsen, M.N.; Ostrowski, M.; Błażewicz-Paszkowycz, M.; Appoh, E.
Abstract: The distribution of cold-water coral reefs is relatively well known in the North-east Atlantic as compared to the Central-east Atlantic, where only a few documentations exist from low latitudes. In 2012 an initial survey was conducted on a reef situated at 400 m depth on the continental shelf off Ghana. The reef corals and fauna were visually documented using a Video Assisted Multi Sampler (VAMS) coupled with an ROV. Here we present the results from three dives on the 1400 m long and 70 m high reef with an ambient temperatures between 9 and 10 °C. The banana shaped reef was oriented perpendicular to the main current, the convex side facing the current and there was no sign of human impact. The great height of the reef is probably a result of undisturbed growth for more than 20, 000 years. On the Norwegian continental shelf the largest reefs are around 30 m high and have been aged to ~9000 years. The reef morphology resembles that of Northeast Atlantic Lophelia reefs. The main reef building coral was Lophelia pertusa with contribution from Madrepora oculata, Solenosmilia variabilis, and occasional occurrences of Dendrophyllia cf. alternata . The skeleton of Aphrocallistes beatrix (Hexactinellidae) contributed to the reef framework and the reef consisted of 46% coral blocks 22% sediment, 13% coral rubble, 11% sponge skeleton and 8% live corals. A rich megafauna of 31 taxa was recorded and most frequent was Acesta excavate (bivalve), Aphrocallistes beatrix (with an associated Zooanthida on 39% of the colonies), squat lobsters, hydroids and bryozoans. Six fish species were recorded of which the Sebastidae Helicolenus dactylopterus and Nettastoma melanurum were found amongst coral blocks. The reef community showed several similarities with the northern reefs with sponges, Sebastes spp., squat lobsters, and Acesta excavata being common megafauna associates. In contrast the gorgonian corals that are characteristic of the northern reefs seemed to be lacking and Hexactinellidae rather than Demospongia were common on the reef and contributed to the reef framework. Crabs that are uncommon on northern reefs were frequently encountered.